Analysis of genetic variability and genotype × year interactions on kernel zinc concentration in selected Indian and exotic maize (Zea mays) genotypes - GULERIA, S K; CHAHOTA, R K; KUMAR, P; KUMAR, A; PRASANNA, B M; HOSSAIN, F; AGRAWAL, P K; GUPTA, H S (The Indian Journal of Agricultural Sciences, 2026)
Analysis of genetic variability for kernel zinc (Zn) concentration was undertaken on 81 maize (Zea mays L.) genotypes, including 13 inbreds from CIMMYT-HarvestPlus, in this study. Kernel Zn concentration varied significantly with a range of 3.81 to 35.83 mg/kg across three years of evaluation (2006-2008). Among the genotypes evaluated during 2006, IML 289 showed highest kernel Zn concentration (35.83 mg/kg), followed by HP 12 (31.69 mg/kg), HP 35-6 (29.02 mg/kg), HP 1 (27.24 mg/kg) and IML 119 (25.77 mg/kg). During kharif 2007, nine genotypes recorded kernel Zn more than 25 mg/kg. Among the landrace accessions, IML 312 (30.30 mg/kg), IML 185 (28.56 mg/kg), IML 288 (26.34 mg/kg), IML 119 (25.88 mg/kg) and IML 390 (25.75 mg/kg) were found promising, while the inbreds BAJIM 06-5 (28.72 mg/kg), CM 145 (25.89 mg/kg), CM 127 (25.45 mg/kg) and BAJIM 06-12 (25.44 mg/kg) recorded kernel Zn concentration. Among the inbreds evaluated during 2008, BAJIM 06-1 (24.74 mg/kg) was identified as the best genotype, followed by V 336(23.36 mg/kg), CM 145 (22.18 mg/kg), CM 140 (21.09 mg/kg), V 340 (20.56 mg/kg), V 348 (20.17 mg/kg) and BAJIM06-6 (20.02 mg/kg). The study revealed significant genotype × year interaction for kernel Zn concentration. Stability analysis revealed that variances due to genotype, year + genotype × year, year (linear) and pooled deviation were significant. Taking into consideration of regression coefficient and deviation from linearity, V 336, VQL 1, V 334 and CM 139 could be identified as stable genotypes for kernel Zn concentration across the years.